Mudança de perspectiva sobre a comunidade LGBTQIAPN+: representatividade nas novelas Brasileiras (1980-2019) - Silva, Luan Vinicius Xavier da (Universidade Federal de São Carlos, 2024)
This work addressed how society and the public changed the way they think about the LGBTQIAPN+ community due to their representation in soap operas shown on different Brazilian broadcasters. To this end, a historical approach to this community since the 1980s will be recovered. If before there was little representation and the characters were often portrayed in a stereotypical way, currently there is greater representation and fewer stereotypes. Although this topic has already been addressed in other academic works, the difference in this approach, in the Brazilian case, is the presence of other broadcasters in addition to Rede Globo. We sought to answer the following question: how did the public and society's thinking change in relation to the LGBTQIAPN+ community with the contribution of soap operas?
Change of perspective on LGBTQIAPN+ community: representation in brazilian sopa operas (1980-2019)
Keywords: LGBTQIAPN+; Comunidade; Representatividade; Community; Representation; CIENCIAS HUMANAS::SOCIOLOGIA